If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + 6 = x + -70 Combine like terms: 16 + 6 = 22 22 = x + -70 Reorder the terms: 22 = -70 + x Solving 22 = -70 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 22 + -1x = -70 + x + -1x Combine like terms: x + -1x = 0 22 + -1x = -70 + 0 22 + -1x = -70 Add '-22' to each side of the equation. 22 + -22 + -1x = -70 + -22 Combine like terms: 22 + -22 = 0 0 + -1x = -70 + -22 -1x = -70 + -22 Combine like terms: -70 + -22 = -92 -1x = -92 Divide each side by '-1'. x = 92 Simplifying x = 92
| 12-3y=14 | | -294-(-70)= | | 10x+70+7x=13+x | | (m-7)=49 | | -1+-5=25 | | -4y+4(4y+4)=8+6(8-y) | | 12x-69=3x+102 | | -.666x(6-3z-7)= | | 23x-3y=5 | | 7-2(x-3)=5-8 | | -1-5=25 | | 6=-32 | | 7(3x-9)=11(4x+7) | | 11x-77=2x+175 | | 16+6=70-x | | 6x+7-2x=4(x+3) | | 2a^2-242=0 | | 7(x+6)-8=5(x-1) | | 22-4(-6.3)=12(-6.3)+126 | | (b+c-1)6= | | 2(-7x+6)-6x=-6 | | x^2+6x-188=0 | | x^2+6x-1880=0 | | y-3=7(x-1) | | -5x-8+4x=-6x-2 | | 25m^2+80m+64= | | -106+4x=141-9x | | 9+-24u+6=u+15 | | y=-4.9x^2+2x+21 | | (4t-q)(-3r)= | | 8x-7=32 | | 13*-9= |